Construction of Agropyron Gaertn. genetic linkage maps using a wheat 660K SNP array reveals a homoeologous relationship with the wheat genome. Issue 3 (16th October 2017) - Zhou, Shenghui; Zhang, Jinpeng; Che, Yonghe; Liu, Weihua; Lu, Yuqing; Yang, Xinming; Li, Xiuquan; Jia, Jizeng; Liu, Xu; Li, Lihui
Summary: Agropyron Gaertn. (P genome) is a wild relative of wheat that harbours many genetic variations that could be used to increase the genetic diversity of wheat. To agronomically transfer important genes from the P genome to a wheat chromosome by induced homoeologous pairing and recombination, it is necessary to determine the chromosomal relationships between Agropyron and wheat. Here, we report using the wheat 660K single nucleotide polymorphism (SNP) array to genotype a segregating Agropyron F1 population derived from an interspecific cross between two cross‐pollinated diploid collections 'Z1842' [ A. cristatum (L.) Beauv.] (male parent) and 'Z2098' [ A. mongolicum Keng] (female parent) and 35 wheat– A. cristatum addition/substitution lines. Genetic linkage maps were constructed using 913 SNP markers distributed among seven linkage groups spanning 839.7 cM. The average distance between adjacent markers was 1.8 cM. The maps identified the homoeologous relationship between the P genome and wheat and revealed that the P and wheat genomes are collinear and relatively conserved. In addition, obvious rearrangements and introgression spread were observed throughout the P genome compared with the wheat genome. Combined with genotyping data, the complete set of wheat– A. cristatum addition/substitution lines was characterized according to their homoeologous relationships. In this study, the homoeologous relationship between the P genome and wheat was identified using genetic linkage maps, and the detection mean for wheat– A. cristatum introgressions might significantly accelerate the introgression of genetic variation from Agropyron into wheat for exploitation in wheat improvement programmes.